Study on the CBN Tool Wear Mechanism on Dry High-Rate Turning Process for AISI 4140 - Harto, Budi; Umroh, Bobby; Darianto, Darianto (JOURNAL OF MECHANICAL ENGINEERING, MANUFACTURES, MATERIALS AND ENERGY, 2018)
This study aims to investigate tools wear and wear mechanisms when machining high-rate extreme minimum lathe AISI 4140 material in hard and dry cutting conditions. Cutting tool made from CBN CB7015 Sandvik Coromant production is used for turning of AISI 4140 steel in order to obtain the failure mode of tool and the wear mechanism of the cutting tool. The machining process is carried out under dry cutting conditions with variations of high velocity Vc, feeding rate f, and a cutting depth a at minimum rate conditions. The wear growth curve obtained shows that the CBN tool undergoes three phases: the initial phase, the gradual phase, and the abrupt phase. From the results of the study found that the failure modes that occur are flank wear, crater wear, flaking, chipping, and fracturing catastrophic failure. The wear mechanism that occurs in outline is caused by abrasive, adhesive, and diffusion processes. While the cracks and fractures that occur due to a combination of impact load and thermal shock